Machilontus (s. str.) medogensis Song & Huang, sp. nov. from Tibet, the northernmost record of the genus Machilontus Silvestri, 1912 and the first record of the family Meinertellidae (Insecta: Microcoryphia: Machiloidea) in China - Song, Zhi-Shun; Huang, Fu-Sheng; Liang, Ai-Ping (Zootaxa, 2011)
A new bristletail species, Machilontus (s. str.) medogensis Song & Huang, sp. nov., is described and illustrated from Medog, Tibet, southwestern China. The new species not only represents the northernmost record of the genus Machilontus Silvestri, 1912, but also represents the first record of the family Meinertellidae Verhoeff, 1910 in China. Checklists of Chinese Microcoryphia and world Machilontus spp. are provided. A distribution map and a key to the species of Machilontus are given.